Fragmente des Balsamierungsrituals in der Eremitage von St. Petersburg - Töpfer, Susanne (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
13 fragments of the recto side of pap. Petersburg ДВ 18128 can be identified as belonging to the ‘Embalming Ritual’. The preserved remains of the papyrus conform exactly to the most extensive source pap. Boulaq 3. It is to be assumed that pap. St. Petersburg ДВ 18128 belongs to pap. Durham 1983.11.